TRAINING OF PENCAK ART TO PRESERVE LOCAL LIFE IN YOUTH ORGANIZATION KP. ANDIR RT. 01 RW. 15 VILLAGE PADALARANG, WEST BANDUNG DISTRICT - Edy Syafrudin; Sri Nurhayati (Empowerment, 2020)
The background of the researchers conducting this research is that the art of pencak art is determined as an intangible cultural heritage by UNESCO so that it hopes that pencak art as an intangible cultural heritage. With this placement, it is expected that young people through youth can continue to cultural background and want to get involved in training conducted as provisions. This training is intended to be able to elevate the art of Pencak among the general public as well as to preserve local culture that has begun to be marginalized in this era of globalization.